2/5x square-x-3/5=0
please answer fast no spam
Answers
Answered by
1
Step-by-step explanation:
Given, 2/5 x2 - x - 3/5 = 0
⇒ 2x2 - 5x – 3 = 0
By splitting the middle term,
⇒ 2x2 - 6x + x – 3 = 0
Taking common in the expression,
⇒ 2x (x - 3) + 1 (x - 3) = 0
⇒ (2x + 1) (x - 3) = 0
∴ 2x + 1 = 0 and ∴ x – 3 = 0
∴ x = -1/2 and ∴ x = 3
Answered by
1
Answer:
Given, 2/5 x2 - x - 3/5 = 0 ⇒ 2x2 - 5x – 3 = 0 By splitting the middle term, ⇒ 2x2 - 6x + x – 3 = 0 Taking common in the expression, ⇒ 2x (x - 3) + 1 (x - 3) = 0 ⇒ (2x + 1) (x - 3) = 0 ∴ 2x + 1 = 0 and ∴ x – 3 = 0 ∴ x = -1/2 and ∴ x = 3
Similar questions